Life history trade-offs assemble ecological guilds. - Bonsall, M; Jansen, V; Hassell, M (2004)
Ecological theory predicts that competition for a limiting resource will lead to the exclusion of species unless the within-species effects outweigh the between-species effects. Understanding how multiple competitors might coexist on a single resource has focused on the prescriptive formalism of a necessary niche width and limiting similarity. Here, we show how continuously varying life histories and trade-offs in these characteristics can allow multiple competitors to coexist, and we reveal how limiting similarity emerges and is shaped by the ecological and evolutionary characteristics of competitors. In this way, we illustrate how the interplay of ecological and evolutionary processes acts to shape ecological communities in a unique way. This leads us to argue that evolutionary processes (life-history trait trade-offs) are fundamental to the understanding of the structure of ecological communities.